Benefícios fiscais de ICMS para a efetivação de direitos fundamentais - REI, José Anijar Fragoso (Universidade Federal do Pará, 2017)
This dissertation relates ICMS (Taxes on Goods and Services) tax benefits and fundamental rights. It will be analyzed whether those benefits that unburden goods and essential services for the realization of fundamental rights must prevail, even if there is no prior agreement signed by the states and the Federal District, as required by article 155, § 2, XII, "g" of the Federal Constitution and Federal Complementary Law n. 24/75. The analysis focuses on the importance of fundamental rights under Brazilian law, as legal principles, therefore, they have high regulatory burden and should guide the interpretation of standards and devices. Therefore, taxation is justified as a source of funding for services and public policies that promote fundamental rights. Moreover, the ICMS (Taxes on Goods and Services) tax benefits should be granted with the safeguards provided in the Fiscal Responsibility Law, without prejudice to combat the use of these instruments to attract economic enterprises, which do not bring the proper return for the rights to the population. However, if the activity benefited provides the realization of fundamental rights effectively, there will be compliance with the existing legal principles. Regarding the ICMS (Taxes on Goods and Services), we conclude that even if the tax benefit was not preceded by covenant of CONFAZ (National Council of Treasury Policy), as required by the Constitution and the LC 24/75, should be considered constitutional, whenever the fundamental rights of the citizen are guaranteed. In reality, the financial burden of this tax falls on the final consumer, then, it is authorized the non- incidence of ICMS (Taxes on Goods and Services) on goods and services which are essential to the enjoyment of rights such as health, education and food.